Rules of the Game of Death Brain - Macedo, Juliana Lopes de (Revista de Antropologia, 2016)
In 1968, the international medical community created the concept of “brain death”, which is presently employed to refer to patients formerly referred to as in “irreversible coma”. Since then, whenever a patient´s brain shows no biological activity while his/her heart still works, the patient is said to be “brainly dead”. For medicine, this implies not only the possibility of organ removal with transplant aims in mind; but also a new form of conceiving death. Based on semi-structured script interviews with medical doctors involved in this predicament, this article analyzes the process regarding brain death and the negotiations among the diverse social agents involved in the process of defining death